Applications of the Dynamic‐Maturational Model of Attachment with Children Involved in Care and Family Proceedings. (3rd April 2015) - Wilcox, Daniel T.; Baim, Clark
Abstract : Attachment theory has had a profound influence on our understanding of human relationships. This paper focuses on the application of the Dynamic‐Maturational Model of attachment to children involved in care and family proceedings. It describes the central principles of attachment as developed by Ainsworth et al. (1978 ); Bowlby (1969 ); Crittenden (2008 ) and Main (1999 ). Attachment patterns are explored and the circumstances under which these various engagement strategies arise. The authors provide two case examples of different insecure attachment styles. They include brief background information, observations about clinical presentation and formulation sections, offering the reader an opportunity to integrate their thinking about how different insecure attachment styles necessitate alternative intervention approaches. The paper highlights the complexity of assessing attachment in different circumstances, and the authors propose that this article should be viewed as a 'primer' for helping practitioners to take better account of attachment issues whenever undertaking assessments within the context of child and family proceedings. Copyright © 2015 John Wiley & Sons, Ltd. 'The paper highlights the complexity of assessing attachment in different circumstances' Key Practitioner Messages: Attachment theory applies to every stage of life. If the baby's care is predictable but not attuned, she learns that thinking protects her and displaying negative emotions endangers her. When the baby's carer is unpredictable and inconsistently attuned, she learns that exaggerating emotions gets results. Mother was unaware that her inconsistency worsened Tammy's behaviour. Anna experienced feelings of self‐blame due to her mother feeling overwhelmed. Assessing attachment can be very complex where a child experiences extended trauma. 'Assessing attachment can be very complex where a child experiences extended trauma'